Currency jumps, cojumps and the role of macro news - Chatrath, Arjun, author; Miao, Hong, author; Ramchander, Sanjay, author; Villupuram, Sriram, author; Journal of International Money and Finance, publisher (Colorado State University. Libraries, 2013)
This study investigates the impact of macro news on currency jumps and cojumps. The analysis uses intra-day data, sampled at 5-min frequency, for four currencies for the period 2005–2010. Results indicate that currency jumps are a good proxy for news arrival. We find 9–15% of currency jumps can be directly linked to U.S. announcements. Notably, news can explain 22–56% of the 5-min jump returns, and there is evidence that better-than-expected news about the U.S. economy has a negative impact on currency jumps. Cojump statistics suggest close dependencies among European currencies, especially between the euro and the Swiss franc. We also provide evidence on the uncertainty resolution to news.
Published as: Journal of International Money and Finance, vol.40, pp.42-62, February 2014, https://doi.org/10.1016/j.jimonfin.2013.08.018.
Keywords: currency jumps; cojumps; macroeconomic news